2016
DOI: 10.1021/acs.jpcc.5b12227
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Stable Surfactant-free Cu5 Clusters in Water

Abstract: We report the synthesis, for the first time, of small, highly monodisperse Cu 5 clusters in water without any surfactant or protective agent. For this purpose, we used a new approach based on the kinetic control of the reaction, which is achieved with an electrochemical method and using a solution with almost no conductivity (i.e., without added electrolytes commonly used in electrochemical methods). This allows the application of extremely small current densities needed to focus the reaction to synthesize onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
72
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 32 publications
4
72
1
3
Order By: Relevance
“…Instead, the presence of a molecule-like HOMO-LUMO gap drastically transforms their chemical and physical properties, thus creating innovative materials for applications including luminescence, 2 sensing, 3 therapeutics, 4 energy conversion, 5 catalysis, 6 and electrochemistry. 7,8 Nowadays, these so-called atomic quantum clusters (AQCs) can be synthesized by kinetic control using electrochemical methods, [9][10][11] showing an exceptional chemical and thermo-dynamical stability in solution over the whole pH range. 9 As discussed in ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the presence of a molecule-like HOMO-LUMO gap drastically transforms their chemical and physical properties, thus creating innovative materials for applications including luminescence, 2 sensing, 3 therapeutics, 4 energy conversion, 5 catalysis, 6 and electrochemistry. 7,8 Nowadays, these so-called atomic quantum clusters (AQCs) can be synthesized by kinetic control using electrochemical methods, [9][10][11] showing an exceptional chemical and thermo-dynamical stability in solution over the whole pH range. 9 As discussed in ref.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Nowadays, these so-called atomic quantum clusters (AQCs) can be synthesized by kinetic control using electrochemical methods, [9][10][11] showing an exceptional chemical and thermo-dynamical stability in solution over the whole pH range. 9 As discussed in ref. 9, high monodispersity of synthesized AQCs (e.g., Cu 5 ) has been achieved since the method of cluster synthesis is extremely size-selective.…”
Section: Introductionmentioning
confidence: 99%
“…Some catalytic reactions may be promoted by atoms or small clusters of copper [11,12]. Huseyinova et al have reported the synthesis of surfactant-free, nearly mono-disperse Cu 5 clusters in water that are stable to UV irradiation, elevated temperature, and a wide range of pH [13]. Their catalytic activity has not yet been measured, but several theoretical studies of water dissociation on Cu 7 have been reported [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[1i] In this context, synthesis and stabilization of CuNCs in an environmentally safe solvent like water is important not only to find ag reen synthesis route, but also for their applications in biosensing and bioimaging. [5] Biomolecules have been attractive stabilizinga gentsf or the synthesis of water soluble CuNCs,W ang and co-workersh ave recently synthesized DNA-hosted CuNCsi na queous medium for identification of their polymorphism. [6] Chattopadhyaya nd co-workersh ave synthesized blue fluorescentC uNCsi na queous mediumfor fluorescent imaging of HeLa cells.…”
Section: Introductionmentioning
confidence: 99%
“…[5h] Therefore, our resultsa re comparable with the other previously reported studies in which smallm olecules have been used as stabilizing agents. From MALDI-TOF analysis, it has been found that the blue CuNC has am olecular formula of Cu 3 (GS), the cyan one is com-posed of two species:C u 5 (GS) 5 and Cu 9 (GS) 5 ,w hereast he green and orange red nanoclustersa re composed of Cu 10 (GS) 9 and Cu 13 (GS) 13 ,r espectively.T he number of Cu atoms for all these CuNCs never exceeds 13. This observation is consistent with the previously reported work by Rivas and co-workers, which describes that only coppern anoclusters in which the number of coppera toms within the nanocluster is 13 show fluorescence.…”
Section: Introductionmentioning
confidence: 99%